Neuroprotective Effects of the Pannexin-1 Channel Inhibitor: Probenecid on Spinal Cord Injury in Rats - Qi, Qi; Wang, Xiao-Xuan; Li, Jing-Lu; Chen, Yu-Qing; Chang, Jian-Rong; Xi, Jin; Lü, He-Zuo; Zhang, Yu-Xin (Frontiers in Molecular Neuroscience, 2022)
Proinflammatory immune cell subsets constitute the majority in the local microenvironment after spinal cord injury (SCI), leading to secondary pathological injury. Previous studies have demonstrated that inflammasomes act as an important part of the inflammatory process after SCI. Probenecid, an inhibitor of the Pannexin-1 channel, can inhibit the activation of inflammasomes. This article focuses on the effects of probenecid on the local immune microenvironment, histopathology, and behavior of SCI. Our data show that probenecid inhibited the expression and activation of nucleotide-binding oligomerization domain receptor pyrindomain-containing 1 (NLRP1), apoptosis-associated speck-like protein containing a CARD (ASC) and caspase-1, interleukin-1β (IL-1β), and caspase-3 proteins associated with inflammasomes, thereby suppressing the proportion of M1 cells. And consequently, probenecid reduced the lesion area and demyelination in SCI. Moreover, the drug increased the survival of motor neurons, which resulted in tissue repair and improved locomotor function in the injured SC. Altogether, existing studies indicated that probenecid can alleviate inflammation by blocking Pannexin-1 channels to inhibit the expression of caspase-1 and IL-1β, which in turn restores the balance of immune cell subsets and exerts neuroprotective effects in rats with SCI.